An Intrinsically‐Adhesive Family of Injectable and Photo‐Curable Hydrogels with Functional Physicochemical Performance for Regenerative Medicine. Issue 10 (8th April 2021) - Karami, Peyman; Nasrollahzadeh, Naser; Wyss, Céline; O'Sullivan, Aine; Broome, Martin; Procter, Philip; Bourban, Pierre‐Etienne; Moser, Christophe; Pioletti, Dominique P.
Abstract: Attaching hydrogels to soft internal tissues is crucial for the development of various biomedical devices. Tough sticky hydrogel patches present high adhesion, yet with lack of injectability and the need for treatment of contacting surface. On the contrary, injectable and photo‐curable hydrogels are highly attractive owing to their ease of use, flexibility of filling any shape, and their minimally invasive character, compared to their conventional preformed counterparts. Despite recent advances in material developments, a hydrogel that exhibits both proper injectability and sufficient intrinsic adhesion is yet to be demonstrated. Herein, a paradigm shift is proposed toward the design of intrinsically adhesive networks for injectable and photo‐curable hydrogels. The bioinspired design strategy not only provides strong adhesive contact, but also results in a wide window of physicochemical properties. The adhesive networks are based on a family of polymeric backbones where chains are modified to be intrinsically adhesive to host tissue and simultaneously form a hydrogel network via a hybrid cross‐linking mechanism. With this strategy, adhesion is achieved through a controlled synergy between the interfacial chemistry and bulk mechanical properties. The functionalities of the bioadhesives are demonstrated for various applications, such as tissue adhesives, surgical sealants, or injectable scaffolds. Abstract : A paradigm shift is proposed for the design of injectable hydrogels that are intrinsically adhesive to various tissues. The innovative mechanism, achieved through the resulting synergy between interfacial chemistry and hydrogel mechanical properties, is demonstrated by varying synthesis parameters and with no extra surface treatment. This universal framework provides a wide window of physicochemical properties required for different biomedical applications.